Exercise Training in Athletes with Bicuspid Aortic Valve Does Not Result in Increased Dimensions and Impaired Performance of the Left Ventricle - Laura Stefani; Giorgio Galanti; Gabriele Innocenti; Roberto Mercuri; Nicola Maffulli (Cardiology Research and Practice)
Background. Bicuspid aortic valve (BAV) is one of the most common congenital heart disease (0.9%–2%) and is frequently found in the athletes and in the general population. BAV can lead to aortic valve dysfunction and to a progressive aortic dilatation. Trained BAV athletes exhibit a progressive enlargement of the left ventricle (LV) compared to athletes with normal aortic valve morphology. The present study investigates the possible relationship between different aortic valve morphology and LV dimensions. Methods. In the period from 2000 to 2011, we investigated a total of 292 BAV subjects, divided into three different groups (210 athletes, 59 sedentaries, and 23 ex-athletes). A 2D echocardiogram exam to classify BAV morphology and measure the standard LV systo-diastolic parameters was performed. The study was conducted as a 5-year follow-up echocardiographic longitudinal and as cross-sectional study. Results. Typical BAV was more frequent in all three groups (68% athletes, 67% sedentaries, and 63% ex-athletes) than atypical. In BAV athletes, the typical form was found in 51% (107/210) of soccer players, 10% (21/210) of basketball players, 10% track and field athletics (20/210), 8% (17/210) of cyclists, 6% (13/210) swimmers, and 15% (32/210) of rugby players and others sport. Despite a progressive enlargement of the LV (P<0.001) observed during the follow-up study, no statistical differences of the LV morphology and function were evident among the diverse BAV patterns either in sedentary subjects or in athletes. Conclusion. In a large population of trained BAV athletes, with different prevalence of typical and atypical BAV type, there is a progressive nonstatistically significant enlargement of the LV. In any case, the dimensions of the LV remained within normal range. The metabolic requirements of the diverse sport examined in the present investigations do not seem to produce any negative impact in BAV athletes